Thermal Comfort for various Altitudes and Land Covers in North Sumatra - Hanny Nirwani; Perdinan; Hidayati, Rini (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2023)
Thermal comfort refers to the suitability of meteorological conditions for humans with the environment. Temperature is the main meteorological variable, which determines the thermal comfort as expressed in various climate indices. This study aims to analysis the distribution of thermal comfort, and to identify environmental factors influencing the comfort situated in North Sumatra, Indonesia. We applied the Universal Thermal Climate Index (UTCI) to determine the heat stress level for 2011 - 2020. The higher UTCI value indicates more uncomfortable conditions related to the higher heat stress. The results showed that the average value of UTCI in North Sumatra was categorised at moderate heat stress. Densely urbanised area in the eastern region contributed to high heat stress, whereas mountainous areas in central to west regions were at low level. Our findings found that climate season affected the distribution of heat stress level. The low heat stress occurred in December-February, while high heat stress happened in June-August. Further, findings revealed that altitude and land cover have contributed to UTCI variation by more than 75% variance.